Attitude stabilization of flexible spacecraft under limited communication with reinforced robustness. (December 2019) - Amrr, Syed Muhammad; Nabi, M
This paper proposes a robust event-driven control for attitude regulation in flexible spacecraft affected by inertial parametric uncertainties and external disturbances. The bandwidth constraint of the communication channel between controller and system requires an event-based control design. Under the action of proposed control law, the system trajectories are ensured to be uniformly ultimately bounded (UUB) in a small vicinity of their equilibrium points. Apart from the boundedness of states, the proposed event-triggered controller also satisfies bandwidth restrictions by achieving a substantially low control usage. The results obtained from numerical simulations are indeed encouraging. It demonstrates the proposed controller as a potential alternative to the periodically sampled data controllers. Moreover, the proposed control strategy successfully eludes the unwanted unwinding phenomenon encountered in quaternion based attitude control of the spacecraft.